Students’ Conceptual Challenges in Learning Multiplication: Tantangan Konseptual Siswa dalam Pembelajaran Perkalian - Putri, Diana; Habibie, Zulqoidi R.; Aldino (Indonesian Journal of Innovation Studies, 2025)
General background: Mathematics is a core subject in elementary schools, yet students often face challenges mastering basic arithmetic operations. Specific background: In Muara Bungo, many fifth-grade students struggle to grasp multiplication concepts, including word problems, operation selection, and decimal placement. Knowledge gap: Few studies have analyzed multiplication difficulties within this local socio-cultural and educational context. Aims: This study aims to identify the types of multiplication-related difficulties, explore their causes, and provide context-specific recommendations. Results: Findings reveal four main difficulties: misinterpretation of problems, incorrect operation selection, errors in decimal placement, and reliance on memorization over understanding. Internal causes include low motivation and self-confidence, while external causes include fast-paced teaching, limited use of concrete media, and minimal parental support. Novelty: This study highlights psychological and contextual factors as the dominant contributors to multiplication difficulties in Muara Bungo’s schools, offering a locally relevant perspective. Implications: The results suggest that teachers should use varied strategies, concrete-to-abstract approaches, and supportive classroom environments, while parents should encourage consistent home practice. Highlights: Many students misunderstand multiplication word problems and rely on memorization. Psychological factors such as fear and low confidence strongly affect learning outcomes. Contextualized, concrete-to-abstract teaching strategies are crucial for conceptual mastery. Keywords: Learning Difficulties, Multiplication, Mathematics Education, Conceptual Understanding, Elementary Students